APPLYING THE INFORMATION-MOTIVATION- BEHAVIORAL SKILLS MODEL IN POSTPARTUM CONTRACEPTION COUNSELING - Nurjanah, Siti; Pangesti, Christiani Bumi; Rumiyati, Eni (International Journal of Psychosocial Rehabilitation, 2020)
Postpartum birth control is essential because the return of fertility in a mother after delivery is unpredictable and can occur before the onset of the menstrual cycle, even in nursing women. The first ovulation in women who are not breastfeeding can occur 34 days postpartum, or even earlier. This causes during breastfeeding, and women often experience unwanted pregnancy (KTD/ unwanted pregnancy) at intervals close to the previous pregnancy. Contraception should have been used before sexual activity begins. It is, therefore, very strategic to start contraception as early as possible after delivery. The method that can be used to change mothers’ awareness and behavior to use postpartum birth control is to provide postpartum contraception counseling using the IMB model approach. The study aimed to analyze the effect of counseling with a model-driven approach to improving information, motivation, and skills in using of postpartum contraception at Gambirsari health centers. This research method uses a quasi-experimental design with a one- group pretest-posttest design model—provision of intervention using the postpartum contraception counseling module with the IMB model approach. This study uses a questionnaire, data collection of information, motivation, and skills to behave in the use of family planning after childbirth. Data analysis using paired T-Test. Data is processed using the software in a computer’s Statistical Product and Service Solution (SPSS) program for windows to facilitate data calculation. The results of the analysis using paired T-Test to determine the effect of counseling with the IMB model approach to the increase in information, motivation and skills using of postpartum contraception obtained a p-value of 0.000 (p <0.05), which means there is an effect of counseling with the IMB model approach to the increase information, motivation, and skills in using of postpartum contraception. This study concludes that there is an effect of counseling with the IMB model approach to improving information, motivation, and skills in using of postpartum contraception.